Winning ideas from Madagascar - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
A project to conserve Madagascar's tapia trees and revive its wild silkworms has won US$110,000 ( 100,000) in the World Bank's 2005 Development Marketplace Competition.